2011
DOI: 10.2741/3673
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanism of Osteoclastogenesis by RANKL and Wnt Signals

Abstract: Osteoclasts develop from monocyte-macrophage lineage cells under the regulation of osteoblasts. Osteoblasts express two cytokines essential for osteoclastogenesis, macrophage colony-stimulating factor (M-CSF) and receptor activator of nuclear factor-KappaB ligand (RANKL). Osteoblasts also produce osteoprotegerin (OPG), a decoy receptor for RANKL, which inhibits the interaction between RANKL and RANK, a receptor of RANKL. Bone resorption-stimulating factors act on osteoblasts to regulate RANKL and OPG expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 50 publications
4
75
0
4
Order By: Relevance
“…A recent study demonstrated that Wnt5a, via noncanonical Wnt signaling, enhanced RANKL-induced osteoclast formation in mouse bone marrow macrophage cultures (50,51). Thus, it is possible that overproduction of Wnt5a in osteoblasts after SCI plays dual roles in unloading related-bone loss by compromising the beneficial role of increased Wnt3a on bone formation after SCI and promoting osteoclastogenesis and bone resorption by increasing RANKL production.…”
Section: Effects Of Sci-and Es-induced Muscle Contraction On Wntmentioning
confidence: 99%
“…A recent study demonstrated that Wnt5a, via noncanonical Wnt signaling, enhanced RANKL-induced osteoclast formation in mouse bone marrow macrophage cultures (50,51). Thus, it is possible that overproduction of Wnt5a in osteoblasts after SCI plays dual roles in unloading related-bone loss by compromising the beneficial role of increased Wnt3a on bone formation after SCI and promoting osteoclastogenesis and bone resorption by increasing RANKL production.…”
Section: Effects Of Sci-and Es-induced Muscle Contraction On Wntmentioning
confidence: 99%
“…VDR and PDIA3 are receptors for 1a,25(OH) 2 D 3 ; osteoprotegerin (OPG) is secreted by differentiated osteoblasts [41]; osteopontin is a 1a,25(OH) 2 D 3 -sensitive extracellular matrix protein that possesses a VDRE [42] and is regulated via PDIA3 [39]; and a2b1 integrin expression is associated with osteoblast differentiation through collagen type 1 recognition [43,44].…”
Section: Embryoid Body Mrna Expressionmentioning
confidence: 99%
“…Among these factors is the crosstalk between osteoprotegerin (OPG), the receptor activator of nuclear factor κ-B (RANK), and its ligand RANKL. OPG can combine with RANKL in competition with RANK, inhibiting the RANKL-RANK system and arresting osteoclasts differentiation [23,25]. Accordingly, the altered balance between OPG and RANKL activity has been shown to play pivotal roles in the development of osteoporosis in animals and man [2].…”
Section: Introductionmentioning
confidence: 99%